Climate variability, agricultural livelihoods and food security in Semiarid Brazil - Mesquita, Patrícia S.; Wittman, Hannah; Aroudo Mota, José (Sustainability in Debate, 2016)
Climate change and variability are among the main threats to socio-ecological sustainability in many semi-arid regions of the world and are of special concern to resource-poor family farmers. In the Brazilian semi-arid region, high levels of social vulnerability in addition to predicted climate events can adversely affect subsistence crops and other cultivated areas with serious consequences for rural food security. An extreme drought that started in 2010 left 174 (of 184) municipalities in the northeastern state of Ceará, Brazil, in a situation of emergency in 2012. During the period of drought, we studied household production characteristics, sources of water for domestic consumption, perception of temperature change and the relationship of those variables with perceived food security. Food security was associated to the presence of piped water and to the diversity of livestock owned by the household. In addition to the importance of observing the role of those variables in public policies related to food security and regional development in the semi-arid region of Brazil, we also highlight the need of understanding the local context where those policies are implemented and the types of local adaptations being performed during periods of shock, which will be recurrent in a scenario of climate change.